Tumor microenvironment and immunotherapy for triple-negative breast cancer - Zijie Guo; Ziyu Zhu; Xixi Lin; Shenkangle Wang; Yihong Wen; Linbo Wang; Lili Zhi; Jichun Zhou (Biomarker Research)
Abstract Triple-negative breast cancer (TNBC) is a subtype of breast cancer known for its high aggressiveness and poor prognosis. Conventional treatment of TNBC is challenging due to its heterogeneity and lack of clear targets. Recent advancements in immunotherapy have shown promise in treating TNBC, with immune checkpoint therapy playing a significant role in comprehensive treatment plans. The tumor microenvironment (TME), comprising immune cells, stromal cells, and various cytokines, plays a crucial role in TNBC progression and response to immunotherapy. The high presence of tumor-infiltrating lymphocytes and immune checkpoint proteins in TNBC indicates the potential of immunotherapeutic strategies. However, the complexity of the TME, while offering therapeutic targets, requires further exploration of its multiple roles in immunotherapy. In this review, we discuss the interaction mechanism between TME and TNBC immunotherapy based on the characteristics and composition of TME, and elaborate on and analyze the effect of TME on immunotherapy, the potential of TME as an immune target, and the ability of TME as a biomarker. Understanding these dynamics will offer new insights for enhancing therapeutic approaches and investigating stratification and prognostic markers for TNBC patients.